Morphometric Analysis of Baitarani Drainage Basin, Odisha - Panda, Siva Prasad (National Geographical Journal of India, 2022)
Basin morphometry is a means of numerically analysing or mathematically quantifying different aspects of a drainage basin. In the present study, an attempt has been made to carryout morphometric analysis of the Baitarani basin.The morphometric parameters considered for analysis include the linear, areal and relief aspects of the basin. The Baitarani basin covers an area of 10,982 sq km. It is a 6th order drainage basin that is characterised with dendritic drainage pattern. The mean bifurcation ratio is 4.58 which indicate that the basin is largely controlled by structure. The basin has medium drainage density of 0.64 per km2 and is elongated in shape. The length of overland flow values of the basin is 3.13, indicating high relief. The study has strengthened in understanding the hydrological, geological and geomorphological characteristics of the Baitarani basin.